The Effects of Online Mindfulness-Based Intervention on Posttraumatic Stress Disorder and Complex Posttraumatic Stress Disorder Symptoms: A Randomized Controlled Trial With 3-Month Follow-Up - Dumarkaite, Austeja; Truskauskaite-Kuneviciene, Inga; Andersson, Gerhard; Kazlauskas, Evaldas (Frontiers in Psychiatry, 2022)
Objectives: Mindfulness-based interventions have recently been shown to be a promising option for treating posttraumatic stress. The current study aimed to investigate the effects of an online mindfulness-based intervention on ICD-11 posttraumatic stress disorder (PTSD) and complex PTSD (CPTSD) symptoms at a 3-month follow-up. Methods: An RCT design with three measurement points (pre-intervention, post-intervention, and 3-month follow-up) was used to investigate the effects of an 8-week online mindfulness intervention. In total, 53 traumatized young adults (Mage=23.21, SDage=2.81; 84.9% female) participated in the study: 17 in the intervention group and 36 in the waiting list control group. Results: Intervention group and waiting list control group comparison revealed that the intervention was effective for reducing CPTSD disturbances in self-organization symptoms (d = -0.84 [-1.44; -0.24]), specifically, negative self-concept (d = -0.66 [-1.25; -0.07]) and disturbances in relationships (d = -0.87 [-1.47; -0.27]), at 3-month follow-up. There were no between-group effects for PTSD symptoms from pre-test to follow-up. Conclusions: This is one of the first RCT studies to report follow-up effects of an online mindfulness-based intervention for ICD-11 PTSD or CPTSD symptoms. Our study yielded that the effects of mindfulness-based internet intervention on CPTSD symptoms tend to retain over time. Trial registration: This study was registered with ClinicalTrials.gov (NCT number: NCT04333667; https://clinicaltrials.gov/ct2/show/NCT04333667). Registered 3rd Apr 2020.